Television and Terror - Hoskins, A. author. aut Link
X, 217 p.
Keywords: The advent of the twenty-first century was marked by a succession of conflicts and catastrophes that demanded unrestrained journalism. Hoskins and O'Loughlin demonstrate that television, tarnished by its economy of liveness and its impositions of immediacy, and brevity, fails to deliver critical and consistent expositions of our conflicting times.